Role of 5-HT3 Receptors in the Antidepressant Response - Connie Sanchez; Bjarke Ebert; Chris Oosterhof; Cécile Bétry; Adeline Etiévant; Nasser Haddjeri (Pharmaceuticals, 2011)
Serotonin (5-HT)3 receptors are the only ligand-gated ion channel of the 5-HT receptors family. They are present both in the peripheral and central nervous system and are localized in several areas involved in mood regulation (e.g., hippocampus or prefrontal cortex). Moreover, they are involved in regulation of neurotransmitter systems implicated in the pathophysiology of major depression (e.g., dopamine or GABA). Clinical and preclinical studies have suggested that 5-HT3 receptors may be a relevant target in the treatment of affective disorders. 5-HT3 receptor agonists seem to counteract the effects of antidepressants in non-clinical models, whereas 5-HT3 receptor antagonists, such as ondansetron, present antidepressant-like activities. In addition, several antidepressants, such as mirtazapine, also target 5-HT3 receptors. In this review, we will report major advances in the research of 5-HT3 receptor’s roles in neuropsychiatric disorders, with special emphasis on mood and anxiety disorders.